Comparison of Direct Examination and In Vitro Culture for the Detection of Blastocystis sp in Orang Asli Stool Samples - Noradilah Samseh Abdullah; Moktar, N; Lee, IL; Salleh, FM; Anuar, TS (Universiti Kebangsaan Malaysia, 2024)
Indexed by WOS/ Scopus